An initial validation of a home–school partnership questionnaire related to teachers' attitudes and actions: Predicting teachers' burnout. Issue 3 (3rd July 2022) - Iida, Junko; Shimada, Naoko; Yamasaki, Saori
ABSTRACT: Home-school partnership is key to students' success at schools. Japanese schools have attempted to invite families to participate in school educational activities. However, these efforts are embedded into Japanese school cultures and were not studied empirically. This study aimed to explore teachers' attitudes and actions toward home–school partnership and examine their effects on teachers' burnout. Based on a preliminary study, we developed a questionnaire with 30 items for the partnership attitude (PAT) scale, 37 items for the partnership actions (PAC) scale and three other scales. We examined the concurrent validity of the scales with a sample of 254 teachers. Exploratory factor analysis yielded four subscales for the PAT (Appreciation, Positive Attitude, Traditional Attitude, Difficulty) and five subscales for the PAC (Respect Parents, Individual Contact, Classroom Information Sharing, Being Proactive, Facilitating Conversation). Reliability was moderately supported, while the criterion validity coefficients were moderately supported using correlation analysis. The results of the multiple regressions show that some PAT factors had negative effects, while some PAC factors had positive effects on teachers' burnout. Thus, while it is important for teachers to build a good home–school partnership through partnership actions, a systematic support system is necessary for teachers experiencing difficulties in collaborating with parents.